Monte Carlo Evaluation of the Impact of Flattening Filter Removal and Collimator on the Energy Properties of a 6 MV Photon Beam Using GATE - I. Lagrini; M. Bencheikh; I. Maouhoubi; A. Khallouqi; H. Sekkat; O. Berradi; M. Bougtib (National Research and Innovation Agency, 2026)
Study aims to evaluate the impact of removing the Flattening Filter (FF) and the secondary collimator on the energetic properties of a 6 MV photon beam. The Monte Carlo (MC) simulation platform GATE/Geant4 (v9.3) was used to evaluate particle fluence, energy fluence distribution, and energy deposited at the phantom surface with a 10 × 10 cm² field size and a Source-to-Surface Distance (SSD) of 100 cm, as well as the production of secondary particles. Validation using Varian Phase-Space (PS) data showed excellent agreement, with gamma pass rates of 99% for Percentage Depth Dose (PDD) and 98% for lateral profiles at depths of 5 and 10 cm, based on a 2% - 2 mm gamma index criterion. Beam quality parameters (TPR20/10) and Relative Dose Differences (RDD) confirmed a margin of error of less than 2%, validating the accuracy of the geometric simulation model. Removing the FF significantly increased the energy fluence of the particles responsible for energy deposition on the surface of the water phantom, increasing relatively by 136% for photons and 55% for electrons in the energy ranges of 0.49 - 0.525 MeV and 0.28 - 0.315 MeV, respectively. Moreover, the secondary collimator contributes significantly to the production of secondary particles that affect the dose distribution and beam energy properties.